2021
DOI: 10.1186/s13287-021-02457-9
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic tracking of 99mTechnetium-labelled equine peripheral blood-derived mesenchymal stem cells after intravenous, intramuscular, and subcutaneous injection in healthy dogs

Abstract: Background Mesenchymal stem cell treatments in dogs have been investigated as a potential innovative alternative to current conventional therapies for a variety of conditions. So far, the precise mode of action of the MSCs has yet to be determined. The aim of this study was to gain more insights into the pharmacokinetics of MSCs by evaluating their biodistribution in healthy dogs after different injection routes. Methods Three different studies wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…In line with the observation in recent studies of our group ( 16 ), no clinical abnormalities or ectopic tissue formations were detected throughout the study. Additionally, after study completion, the investigator remained in contact with the dog owner and no clinical abnormalities were reported since.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with the observation in recent studies of our group ( 16 ), no clinical abnormalities or ectopic tissue formations were detected throughout the study. Additionally, after study completion, the investigator remained in contact with the dog owner and no clinical abnormalities were reported since.…”
Section: Discussionsupporting
confidence: 92%
“…Our group recently reported the tracking of radiolabelled ePB-MSCs following intravenous, intramuscular and subcutaneous administration in healthy dogs. In that study, radiopharmaceutical uptake was predominantly seen in the heart, lung, liver and bladder ( 16 ). To the author's knowledge, no study has reported the tracking of MSCs in dogs suffering from orthopedic lesions.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…As an adult stem cell, they exist in organ stroma and connective tissue with strong proliferation ability [ 7 ]. When in a suitable environment, they can differentiate into a variety of cells, such as osteoblasts [ 8 , 9 ]. Therefore, they also show a certain multidirectional differentiation potential and can be separated from bone marrow and other tissues [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent stromal cells from adult tissues that have the capability of differentiating in different cell lineages [ 7 ]. Umbilical Cord MSCs (UCMSCs) is one of the ideal sources of MSCs, which are attractive for clinical use [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%